2017
DOI: 10.21474/ijar01/3915
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Machinability Characteristics Under Minimum Quantity Lubrication Using Graphene Based Nano-Cutting Fluid.

Abstract: Minimum quantity lubrication (MQL) has proved to be a sustainable method which can replace flood cooling for the application of cutting fluid in the metal cutting operation. Addition of nanoparticles in the cutting fluid may enhance the cooling and lubricating properties of the base fluid. Present work deals with the experimental investigation of the effect of addition of graphene nanoparticles in the cutting fluid under MQL on machinability characteristics such as tool flank wear, surface roughness and cuttin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…They observed that feed was the most important parameter for roughness and MQL with nanofluid produced better result in comparison to other three cutting conditions. Singh et al [16] experimentally investigated the machinability characteristics of AISI 304 stainless steel under nano-lubrication using MQL technique. Various machining characteristics such as flank wear, cutting zone temperature and surface roughness were studied.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that feed was the most important parameter for roughness and MQL with nanofluid produced better result in comparison to other three cutting conditions. Singh et al [16] experimentally investigated the machinability characteristics of AISI 304 stainless steel under nano-lubrication using MQL technique. Various machining characteristics such as flank wear, cutting zone temperature and surface roughness were studied.…”
Section: Introductionmentioning
confidence: 99%